A high-performance protein crystallization plate pre-embedded with crosslinked protein microcrystals as seeds. Issue 33 (26th July 2018) - Hou, Hai; Shi, Miao; Chen, Zhong-Hao; Ahmad, Fiaz; Liu, Yue; Yan, Er-Kai; Luo, Chao; Li, Jing; Zhu, Cheng-Long; Deng, Xu-Dong; Yin, Da-Chuan
Abstract : The high performance and stability of the microcrystals suggested that the novel plate can be practically applied in routine protein crystallization. Abstract : The wells of the novel plate are pre-embedded with cross-linked protein microcrystals which can act as the seeds for protein crystallization. The results of crystallization screening experiments showed that the novel plate exhibited dramatically improved performance in finding crystallization conditions as compared with the original CDM plate.